Murmur intensity in adult dogs with pulmonic and subaortic stenosis reflects disease severity. (11th October 2017) - Caivano, D.; Dickson, D.; Martin, M.; Rishniw, M.
Abstract : Objectives: The aims of this study were to determine whether murmur intensity in adult dogs with pulmonic stenosis or subaortic stenosis reflects echocardiographic disease severity and to determine whether a six‐level murmur grading scheme provides clinical advantages over a four‐level scheme. Materials and Methods: In this retrospective multi‐investigator study on adult dogs with pulmonic stenosis or subaortic stenosis, murmur intensity was compared to echocardiographically determined pressure gradient across the affected valve. Disease severity, based on pressure gradients, was assessed between sequential murmur grades to identify redundancy in classification. A simplified four‐level murmur intensity classification scheme ('soft', 'moderate', 'loud', 'palpable') was evaluated. Results: In total, 284 dogs (153 with pulmonic stenosis, 131 with subaortic stenosis) were included; 55 dogs had soft, 59 had moderate, 72 had loud and 98 had palpable murmurs. 95 dogs had mild stenosis, 46 had moderate stenosis, and 143 had severe stenosis. No dogs with soft murmurs of either pulmonic or subaortic stenosis had transvalvular pressure gradients greater than 50 mmHg. Dogs with loud or palpable murmurs mostly, but not always, had severe stenosis. Stenosis severity increased with increasing murmur intensity. The traditional six‐level murmur grading scheme provided no additional clinical information than the four‐level descriptive murmur grading scheme. Clinical Significance: A simplified descriptive four‐level murmur grading scheme differentiated stenosis severity without loss of clinical information, compared to the traditional six‐level scheme. Soft murmurs in dogs with pulmonic or subaortic stenosis are strongly indicative of mild lesions. Loud or palpable murmurs are strongly suggestive of severe stenosis.